An ancient Wnt-Dickkopf antagonism in Hydra - Guder, Corina; Holstein, Thomas W. (Development, 2006)
The dickkopf (dkk) gene family encodes secreted antagonists of Wnt signalling proteins, which have important functions in the control of cell fate, proliferation, and cell polarity during development. Here, we report the isolation, from a regeneration-specific signal peptide screen, of a novel dickkopf gene from the fresh water cnidarian Hydra. Comparative sequence analysis demonstrates that the Wnt antagonistic subfamily Dkk1/Dkk2/Dkk4 and the non-modulating subfamily Dkk3 separated prior to the divergence of cnidarians and bilaterians. In steady-state Hydra, hydkk1/2/4-expression is inversely related to that of hywnt3a. hydkk1/2/4 is an early injury and regeneration responsive gene, and hydkk1/2/4-expressing gland cells are essential for head regeneration in Hydra, although once the head has regenerated they are excluded from it. Activation of Wnt/β-Catenin signalling leads to the complete downregulation of hydkk1/2/4 transcripts. When overexpressed in Xenopus, HyDkk1/2/4 has similar Wnt-antagonizing activity to the Xenopus gene Dkk1. Based on the corresponding expression patterns of hydkk1/2/4 and neuronal genes, we suggest that the body column of Hydra is a neurogenic environment suppressing Wnt signalling and facilitating neurogenesis.